Habituation and rebound to thalamic deep brain stimulation in long-term management of tremor associated with demyelinating neuropathy. (1st December 2014) - Patel, Neepa; Ondo, William; Jimenez-Shahed, Joohi
<x xml:space="preserve">Abstract</x> Some patients may experience tolerance to chronic ventral intermediate (ViM) thalamic deep brain stimulation (DBS), which may include habituation (loss of sustained tremor control over weeks to days after an adjustment) and rebound (a temporary increase in tremor intensity after stopping DBS). We observed an association between these efficacy limiting phenomena with co-morbid demyelinating sensorimotor peripheral neuropathy (MRT-PN). The clinical and treatment characteristics of neuropathy and tremor pre- and post-DBS are described through retrospective chart review of five patients with MRT-PN. Programming strategies (number of programming visits/implant years and number of major parameter changes/electrode) were compared in MRT-PN patients to a group of seven ET patients without neuropathy, who had >4 years continuous follow-up. The presence of habituation and rebound were recorded. All MRT-PN patients had initial good response to DBS followed by habituation and/or rebound of tremor control, some asymmetrically. Compared to ET without neuropathy (mean follow-up 5.83 ± 0.78 years), MRT-PN patients (mean follow-up 4.90 ± 3.73years) required more programming visits/year (p = 0.12) and major parameter changes/electrode/implant year (p = 0.03). The presence of neuropathy may alter tremor characteristics and result in temporary re-setting of thalamic oscillatory drive after DBS in MRT-PN patients. Clinicians should be aware of the risk for tolerance to DBS in MRT-PN and patients should be counseled about possible suboptimal sustained tremor control.